ANALISIS PENGARUH BAURAN PEMASARAN HOLISTIK TERHADAP LOYALITAS NASABAH TABUNGAN PADA BANK X - Indra Maulana; Mohammad Fahmi Arkanuddin (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study uses a quantitative-descriptive approach, with SPSS 22 analysis tool to test the model. This study was conducted to analyze the significance of the influence of holistic marketing mix variables, namely product, price, promotion, place people, process, program and performance on customer loyalty savings. Holistic marketing mix variables have a significant effect on customer loyalty savings, namely: product, price, people and performance, while the variables that have no significant effect are: promotion, place, process and program. The coefficient of determination or R is 0.955, this indicates that the holistic marketing mix is ​​able to affect customer loyalty savings by 95.50% of which 4.50% is influenced by other variables not examined. Banks can focus on 4 (four) significant variables by improving the performance of product, price, people and performance variables, namely in terms of making strategies, business plans and work programs to increase savings customer loyalty, so as to increase benefits and profits for banks both for the time being. this time and in the future, meanwhile, banks can improve the performance of promotion, place, process and program, so that they can contribute positively to savings performance.